2019
DOI: 10.5430/jnep.v9n5p44
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about breast and cervical cancers among nursing students in Beni-Suef University

Abstract: Background and objective: Breast and cervical cancers represent a public health concern since they result in high mortality and disability rates. The aim of our study was to assess the knowledge of nursing students in Beni-Suef University about both Breast and cervical.Subjects and methods: A total of 500 students representing all scholastic years from the Technical Institute of Nursing (both 2 years of post-high school nursing education), Beni-Suef University, Egypt, participated in this study that was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…[27] Therefore, it is crucial for nurses to be aware of adequate and necessary knowledge in order to conduct their future tasks, as nurses, appropriately. [28] As nurses comprise the greatest portion of the health care system, they are the key persons in the healthcare delivery system. The current study was conducted to determine the impact of PCOS on women's QOL through the following mentioned objectives:…”
Section: Aim Of This Studymentioning
confidence: 99%
“…[27] Therefore, it is crucial for nurses to be aware of adequate and necessary knowledge in order to conduct their future tasks, as nurses, appropriately. [28] As nurses comprise the greatest portion of the health care system, they are the key persons in the healthcare delivery system. The current study was conducted to determine the impact of PCOS on women's QOL through the following mentioned objectives:…”
Section: Aim Of This Studymentioning
confidence: 99%
“…This may attribute to rural areas are healthier and less exposed to prolusion and psychological stressors which in-turn affects the quality of life and sexual life as well. Previous studies found that depression and/or anxiety were observed more in housewives than in outside employees [37][38][39]. Moreover, Shifren, et al [40] Hayes, et al [37] found that psychological disorders being more common in housewives than in working ones [41].…”
Section: Discussionmentioning
confidence: 96%
“…Cervical cancer is a type of cancer that occurs in the cells of the cervix. Various strains of the human papillomavirus (HPV), sexually transmitted infections, play a vital role in causing most cervical cancer [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the treatment process, the nurse follows the progress of the patient and acts accordingly with the patient's best interests in mind. The care provided by a nurse extends beyond the administration of medications and other therapies; nurses are responsible for the holistic care of patients [13]. The nurse also guides the cervical cancer survivor to regain self-confidence and adapt to physical and psychological changes to optimize survivor autonomy [1].…”
Section: Introductionmentioning
confidence: 99%